EFEKTIFITAS HAND LETTERING SEBAGAI MEDIA PROMOSI KESEHATAN REMAJA MENGENAI BAHAYA ROKOK (STUDI DI SMK PGRI 4 SURABAYA) - Azmi Luthfia; Pulung Siswantara (The Indonesian Journal of Public Health, 2018)
Indonesia is a country with largest smoker in South East Asia. According to Riset Kesehatan Dasar (RISKESDAS) (2013), there is rising trends of cigarette smooking during three periods, especially in adolescents aged ≥15 years. Therefore it is necessary to take effort to prevent existence of it. Providing health promotion media in the form of hand lettering can be an alternative in providing effective information and education. Now days, Hand lettering is a popular art design for adolescents. This research was conducted on the students of class XI TKR SMK PGRI 4 Surabaya. The purpose of this study was to know the efectiveness of hand lettering as a health promotion media of harmfull effect of cigarettes in adolescents. It was quasi experimental research. Samples are 90 students of class XI TKR SMK PGRI 4 Surabaya, taken by  total sampling technique. Knowledge was dependent variable, while giving treatments was independent variables. Results showed that there were differences knowledge betwween before and after hand lettering given (p = 0,000). Media effectiveness shows that hand lettering is effective for improving knowledge. It can be used as a health promotion media of harmfull effect of cigarettes in adolescents.